Truth and History:: Representing the Aura in The Englishman’s Boy - Janes, Daniela (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
In Guy Vanderhaeghe's The Englishman's Boy, three modes of representation, oral, visual, and written, tie together five interrelated stories that span eighty years. Because of its shifting present, the novel reassures the reader of its own reliability within the hermetic world of the text; simultaneously, however, Vanderhaeghe throws doubt on the possibility of ever adequately representing history. In a sense, Vanderhaeghe's depiction of historical truth as elusive and unreproducible parallels Walter Benjamin's notion of the aura: the mystical, intangible, and unreproducible quality in a work of art that distinguishes it from other works and from copies of itself. Representation becomes, for Vanderhaeghe, an impossible attempt to recapture a truth that absents itself as soon as the historical moment has passed.